Cancer as a System Dysfunction - Khalid Saeed; Elizabeth F. Ryder; Amity L. Manning (Systems, 2021)
In this paper, we describe a system dynamics model that views cancer as a dysfunction of the cellular system rather than as an ailment of cells. Our experiments with the model replicate the propagation of the ailment and the impacts of the treatments. It presents a concept that deviates from the pervasive view of cancer as a cell malfunction that has led to treatments aiming to destroy the rogue cells. It points to more holistic treatment options aiming at reforming cell interaction so the system can contain the growth of cancer cells. Further research is needed to explore the details for such options.